2009
DOI: 10.1111/j.1365-2826.2009.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Vasopressin and Oxytocin mRNA Expression in Relation to Depressive State in Alzheimer’s Disease: A Difference With Major Depressive Disorder

Abstract: Arginine vasopressin (AVP) and oxytocin (OXT), produced in the hypothalamic paraventricular (PVN) and supraoptic nucleus (SON), are considered to be involved in the pathophysiology of major depressive disorder (MDD). The objective of this study was to determine, for the first time, the relationship between AVP and OXT gene expression and depressive state in Alzheimer's disease (AD). Post-mortem brain tissue was obtained from six control subjects, and from a prospectively studied cohort of 23 AD patients, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Exposure to stress can result in an increase in the stress hormone cortisol through the central HPA system [44], and the patients with AD with a higher dysphoria score had a higher Research Yu San Chang cortisol level in our results, which may suggest that the patients subjectively experienced more stress. The experience of stress is known to exacerbate mental illness, thereby contributing to the risk of depression [45].…”
Section: Discussionsupporting
confidence: 56%
“…Exposure to stress can result in an increase in the stress hormone cortisol through the central HPA system [44], and the patients with AD with a higher dysphoria score had a higher Research Yu San Chang cortisol level in our results, which may suggest that the patients subjectively experienced more stress. The experience of stress is known to exacerbate mental illness, thereby contributing to the risk of depression [45].…”
Section: Discussionsupporting
confidence: 56%
“…The AVP mRNA in the SON is also increased in depressed subjects (339). In contrast, AVP mRNA expression in the PVN and SON is unchanged in depressed patients with Alzheimer's disease compared with nondepressed patients with Alzheimer's disease (338). Interestingly, two studies found a correlation between plasma AVP levels and cortisol levels in depression, particularly in suicide victims (112,232), but this finding was contradicted by another report (75).…”
Section: Anxiety and Depressionmentioning
confidence: 44%
“…Several studies have highlighted the role of oxytocin and vasopressin in social recognition3,4 and show that low levels of oxytocin could be responsible for deficits in face recognition in autistic patients 5. However, in AD patients, postmortem studies failed to show differences in central vasopressin and oxytocin concentration6 except in the hippocampus where levels were higher than in normal patients 7. This indicates that variations in oxytocin levels do not underlie the deficit in social recognition in AD and points to our incomplete understanding of the neural circuitries responsible for social recognition.…”
Section: Introductionmentioning
confidence: 99%